CURRENT AND FUTURE APPROACHES TO THE DIAGNOSIS OF NON-ALCOHOLIC FATTY LIVER DISEASE - Parpibaeva D. A.; Buvamukhamedova N. T.; Salaeva M. S.; Boltaboev X. Q.; Turbanova U. V. (Journals Park Publishing, 2023)
Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver disease, are prone to a progressive flow. NAFLD is a diagnosis of exclusion, and therefore rational diagnosis of this disease is based on a combination of clinical, laboratory and instrumental data. The article provides an overview of current and prospective methods of diagnosis of NAFLD. The role of biomarkers as a promising non-invasive diagnostic tools for assessing the severity of necroinflammatory and hepatic fibrosis in patients with NAFLD.
Keywords: non-alcoholic fatty liver disease, SFRP4, non-alcoholic steatohepatitis, steatosis, fibrosis of the liver, cirrhosis of the liver.